Taxonomy and morphology of Cladochaeta Coquillett, 1900 in Brazil (Diptera: Drosophilidae: Drosophilinae) - Ignácio, Gabriela Pirani (2015)
Drosophilidae is a very diverse family of acalapytrate flies comprising more than 4,000 described species, worldwide in distribution, occupying a large range of ecological niches and with high morphological variability. Despite the huge number of papers published on different aspects of the genus Drosophila Fallen, 1823 and especially D. melanogaster Meigen, 1830, the group as a whole can still be considered poorly known, since some taxa within it have historically gained more attention than others. As one of the examples of a very speciose but unsatisfactorily studied group, is the drosophiline genus Cladochaeta Coquillet, 1900, with more than 100 described Neotropical and some few southern Nearctic species, but still with a large number of species to be described. In this study the Brazilian fauna of the genus is revised, with the description of 16 new species based on malesCladochaeta sp. 1, nov. sp., C. sp. 2, nov. sp., C. sp. 3, nov. sp., C. sp. 4, nov. sp., C. sp. 5, nov. sp., C. sp. 6, nov. sp., C. sp. 7, nov. sp., C. sp. 8, nov. sp., C. sp. 9, nov. sp., C. sp. 10, nov. sp., C. sp. 11, nov. sp., C. sp. 12, nov. sp., C. sp. 13, nov. sp., C. sp. 14, nov. sp. and C. sp. 15, nov. sp. The descriptions include photographs for each species and detailed illustrations of the male terminalia in different views. A synopsis about the taxonomy and natural history of the genus, a key for the Brazilian species, and a distributional map of the genus in Brazil are provided. Some comments about relationships between some of the species of the genus are made, as well as a discussion about male terminalia sclerite homology, and the issue of association between males and females.